Measuring the spillovers of US unconventional surprises across monetary conditions with local projections - Arisa Chantaraboontha (Osaka University, Institute of Social and Economic Research (ISER), 2025)
This paper examines the responses of foreign exchange rates to the Federal Reserve's large-scale asset purchases (LSAPs) and forward guidance (FWG) from 2009 to 2022 using local projections. I confirm heterogeneous responses of examined foreign exchange rates to unconventional shocks, varying by magnitude, direction, and duration depending on monetary policy conditions and the type of shock. Both shocks caused the appreciation of foreign exchange rates against the US Dollar in all monetary policy cycles, except for the FWG shock during normalization periods of monetary policy. The FWG shock had a greater impact magnitude on the examined foreign exchange rates than the LSAPs shock. The effects of both unconventional shocks were more persistent during periods of zero lower bound (ZLB) on the policy interest rate than during normalization periods of monetary policy. However, the impact of such shocks on foreign exchange rates diminished within a couple of months, contrasting with the literature that finds more persistent effects. The implementation of variance decomposition reveals that the FWG shock had a significantly greater influence on foreign exchange rate variation than the LSAPs shock, emphasizing the importance of effective guidance communication to the markets.
Keywords: 330; Federal Reserve; Unconventional monetary shocks; Large-scale asset purchases; Forward guidance; Euro; Japanese Yen; Thai Baht; Malaysian Ringgit